O sensacionalismo na visão poética de Álvaro de Campos - D'Onofrio, Salvatore [UNESP]; Árabe, Maria Amália A. [UNESP] (Universidade Estadual Paulista (Unesp), 1980)
Trata-se de um estudo sobre a poética do heterônimo Álvaro de Campos, expressão artística de Fernando Pessoa, voltado para a compreensão do mundo moderno, dominado pela tecnologia. O centro desta poética é encontrado no processo de intelectualização das sensações, visto como meio quer de autognose quer de compreensão da realidade. This is a study on the poetics of the heteronym Álvaro de Campos, Fernando Pessoa’s artistic expression concerned with the understanding of the modern world dominated by technology. The centre of this poetics is found in the process of intellectualization of sensations, which is seen as means either of self-knowledge or of understanding of reality
Sensationism in Álvaro de Campos, poetical vision
Keywords: Teoria da literatura; Literatura portuguesa; Fernando Pessoa; Poesia; Literary Theory; Portuguese literature; Fernando Pessoa; Poetry